A Comment on Business Policy Teaching Research - Snow, Charles C. (Academy of Management Review, 1976)
In this article the author provides comments on research that has examined the effectiveness of several different approaches to teaching business policy. The author discusses four educational formats that have been studied and notes the weaknesses associated with each study. The formats examined make use of case studies, simulation methods, in-class activities and variations that include multiple methods. The author's main concerns deal with addressing what students should learn in a business policy course, how these courses should be taught and how teaching methods can be compared. He notes that most research has focused on how to teach, rather than on what to teach and that students will benefit more by determining what is most important for them to learn.